Evidence for the Packaging of Multiple Copies of Tf1 mRNA into Particles and the trans Priming of Reverse Transcription - Haag, Amanda Leigh (American Society for Microbiology, 2000)
Long terminal repeat (LTR)-containing retrotransposons and retroviruses are close relatives that possess similar mechanisms of reverse transcription. The particles of retroviruses package two copies of viral mRNA that both function as templates for the reverse transcription of the element. We studied the LTR-retrotransposon Tf1 of Schizosaccharomyces pombe to test whether multiple copies of transposon mRNA participate in the production of cDNA. Using the unique self-priming property of Tf1, we obtained evidence that multiple copies of Tf1 mRNA were packaged into virus-like particles. By coexpressing two distinct versions of Tf1, we found that the bulk of reverse transcription that was initiated on one mRNA template was subsequently transferred to others. In addition, the first 11 nucleotides of one mRNA were able to prime, in trans, the reverse transcription of another mRNA.